Transcranial Direct Current Stimulation on Parkinson's Disease: Systematic Review and Meta-Analysis - Oliveira, Paloma Cristina Alves de; Araújo, Thiago Anderson Brito de; Machado, Daniel Gomes da Silva; Rodrigues, Abner Cardoso; Bikson, Marom; Andrade, Suellen Marinho; Okano, Alexandre Hideki; Simplicio, Hougelle; Pegado, Rodrigo; Morya, Edgard (Frontiers in Neurology, 2022)
Background: Clinical impact of transcranial Direct Current Stimulation (tDCS) alone for Parkinson's Disease (PD) is still a challenge. Thus, there is a need to synthesize available results, analyze methodologically and statistically, and provide evidence to guide tDCS in PD. Objective: Investigate isolated tDCS effect in different brain areas and number of stimulated targets on PD motor symptoms. Methods: A systematic review was carried out up to February 2021, in databases: Cochrane Library, EMBASE, Pubmed/MEDLINE, Scopus and Web of science. Full text articles evaluating effect of active tDCS (anodic or cathodic) versus sham/control on motor symptoms of PD were included. Results: Ten studies (n=236) were included in meta-analysis and 25 studies (n=405) in qualitative synthesis. The most frequently stimulated targets were Dorsolateral Prefrontal Cortex and Primary Motor Cortex. No significant effect was found among single targets on motor outcomes: Unified Parkinson's Disease Rating Scale (UPDRS) III - motors aspects (MD= -0.98%, 95% CI= -10.03 to 8.07, P= 0.83, I²= 0%), UPDRS IV - dyskinesias (MD= -0.89%, CI 95%= -3.82 to 2.03, P= 0.55, I² = 0%) and motor fluctuations (MD= -0.67%, CI 95%= -2.45 to 1.11, P= 0.46, I² = 0%), timed up and go - gait (MD= 0.14%, CI 95%= -0.72 to 0.99, P= 0.75, I² = 0%), berg balance scale - balance (MD= 0.73%, CI 95%= -1.01 to 2.47, P= 0.41, I² = 0%). There was no significant effect of single versus multiple targets in: UPDRS III - motors aspects (MD= 2.05%, CI 95%= -1.96 to 6.06, P= 0.32, I² = 0%) and gait (SMD= -0.05%, 95% CI= -0.28 to 0.17, P= 0.64, I² = 0%). Simple univariate meta-regression analysis between treatment dosage and effect size revealed that number of sessions (estimate = -1.7, SE = 1.51, z-score = -1.18, p = 0.2, IC= -4.75 to 1.17) and cumulative time (estimate = -0.07, SE = 0.07, z-score = -0.99, p = 0.31, IC= -0.21 to 0.07) had no significant association. Conclusion: There was no significant tDCS alone short-term effect on motor function, balance, gait, dyskinesias or motor fluctuations in Parkinson's Disease, regardless of brain area or targets stimulated.